2002
DOI: 10.1103/physrevlett.89.187602
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity and Isotope Effects in Hydrogen-Bonded KDP Crystals

Abstract: Based on an accurate first principles description of the energetics in H-bonded KDP, we conduct a first study of nuclear quantum effects and of the changes brought about by deuteration. Cluster tunneling involving also heavy ions is allowed, the main effect of deuteration being a depletion of the proton probability density at the O-H-O bridge center, which in turn weakens its protonmediated covalent bonding. The ensuing lattice expansion couples selfconsistently with the proton off-centering, thus explaining b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
96
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 58 publications
14
96
0
1
Order By: Relevance
“…This picture is challenged by experimental work giving evidence of a proton delocalization along the O-H-O bonds above T C (7). Recent ab initio calculations suggest a prominent role of electronic charge redistributions and ionic displacements that are linked to proton ordering in the ferroelectric phase (9,21). Lattice vibrations involved in the phase transition have been studied by steady-state infrared and Raman spectroscopies.…”
Section: Methodsmentioning
confidence: 99%
“…This picture is challenged by experimental work giving evidence of a proton delocalization along the O-H-O bonds above T C (7). Recent ab initio calculations suggest a prominent role of electronic charge redistributions and ionic displacements that are linked to proton ordering in the ferroelectric phase (9,21). Lattice vibrations involved in the phase transition have been studied by steady-state infrared and Raman spectroscopies.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary effects are those where the X-Y bond length changes, and are also known as the Ubbelöhde effect [53]. There have been extensive experimental [54][55][56][57][58] and theoretical [36,[59][60][61][62][78][79][80][81][82][83] investigations of these geometric isotope effects.…”
Section: Isotope Effectsmentioning
confidence: 99%
“…It was shown that the proton ordering model provides a satisfactory description of the available experimental data for pressure and field dependences of physical characteristics of the KH 2 PO 4 family ferroelectrics. Validity of the proton ordering model for the KH 2 PO 4 family crystals was also indicated in [181][182][183][184].…”
Section: Introductionmentioning
confidence: 99%